The Representation of Multicultural Education in Film “Raya and The Last Dragon” - Muflikhah Ulya; Muhammad Altaf Rezaian (UM Purwokerto Press, 2022)
The film is one of the media that represents the multicultural concept. Representation in films can create a paradigm that indirectly influences the audience's mindset. Among various genres of film, film animation is one genre that can attract the attention of various levels of society of all ages. Animated films are easier to accept because they have a weak storyline and are full of moral messages. One of the public's animated films in great demand is